o uso do paradigma restrições geométricas para apoio a projetos de instalações elétricas - Silva, Arquimedes Lopes da (2006)
Nowdays, a growth has been observing in the software use CAD (Computer-Aided Design) and CAE (Computer-Aided Engineering) for design in area of the architecture, engineering and building . The professional makes use of those tools that automate and accelerate design routines propitiating more time to improve the quality of them. However, most of the current systems not only consumes time of processing (once all the calculations are re-done in order to increase or to remove information of the design), as they require that the designer keeps in mind the design sequence what limits his/her creativity of testing different design alternatives. Recently, CAD/CAE designs has explored the use of the constraints paradigm for the development of its support tools. Through this approach, the engineer creates his/her designs establishing geometric constraints (geometric relationships among the entities of the drawing) and/or engineering constraints (equations that reflect physical laws as performance, power etc) among the entities of the drawing. The way of constraints satisfaction during the building of the design is that propitiates again in terms of answer time regarding the system interaction with the designer. However, current tools that work with this approach don't present applications in the area of electrical installation design. This is verified in this work through an in- vestigative study of current tools, trying to highlight the advantages as decrease of repetitive tasks and the limitations as the engineer's dependence in the building of the tubulation through where it will pass the conductors of the several electric circuits, ma- nual calculation of the lower tubulation path (what would contribute to better design energetic efciency). Based on these limitations the building of a system geometric constraints-based for the area of residential electrical installation design is proposed, so that it assists to the market needs and that makes possible future integration among the several designs of building installation. For this reason, incremental graph-based algorithms were developed so that they allow the construction of the drawing taking advantage of what it was already drawn. The algorithms allow to create electrical installation design starting from the location of the energy points with its connecti- ons as switches, conduits and conductors, and, at the same time, they facilitate the dimensioning of these connections calculations. The prototype system presents new features such as the migration for 3D designs, the automatic launching of tubulation and wires, among other. Such characteristics increase the engineer designer's productivity. This productivity is due to the flexibility of the incremental algorithms and the use of three-dimensional environment allowing an immediate understanding of what is happening during the building of the design. This environment can be developed into a virtual environment which can provides a better space understanding, reducing, consequently, the time of analysis.